Validation of the PBIS-ACT Full: An Updated Measure of Staff Commitment to Implement SWPBIS. (February 2019) - Filter, Kevin J.; Brown, Jeffrey
School-wide positive behavior interventions and supports (SWPBIS) relies on the implementation efforts of frontline service providers such as teachers, administrators, and staff. The full version of the positive behavior interventions and supports–action and commitment tool (PBIS-ACT Full) measures the individual implementer variable of commitment to implement SWPBIS. The purpose of the present study was to evaluate the validity and reliability of the PBIS-ACT Full in relation to a previous brief version of the measure. Results indicated that the factor structure closely mirrors the original theoretical design of the PBIS-ACT Full. The measure demonstrated strong internal consistency and was more sensitive to differences in commitment on the high end of the scale when compared with scores from the previous version. Based on the present results, the PBIS-ACT Full demonstrates strong potential to facilitate research and practice relating to staff commitment to implement SWPBIS.